2014
DOI: 10.1371/journal.pone.0113915
|View full text |Cite
|
Sign up to set email alerts
|

Association between Serum Chemerin Concentrations and Clinical Indices in Obesity or Metabolic Syndrome: A Meta-Analysis

Abstract: ObjectiveChemerin is a novel adipokine. Previous research has investigated the association between chemerin and clinical indices in patients with obesity or metabolic syndrome (MS), although the results obtained have been inconsistent. We conducted a meta-analysis to investigate the association between chemerin and clinical indicators of diabetes, MS and obesity with obesity or MS subjects.Design and MethodsStudies were identified by searching the PubMed, the Cochrane Library, EMBASE and CNKI, databases beginn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
60
4
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(73 citation statements)
references
References 30 publications
8
60
4
1
Order By: Relevance
“…[13][14][15] In line with others, we found high chemerin levels to correlate with T2DM and low high-density lipoprotein. 13,14 Furthermore, a positive correlation was observed between chemerin and macrophage inflammatory protein 1-α, which is known to be involved in atherogenesis.…”
Section: Dual Action Of Chemerinsupporting
confidence: 88%
See 1 more Smart Citation
“…[13][14][15] In line with others, we found high chemerin levels to correlate with T2DM and low high-density lipoprotein. 13,14 Furthermore, a positive correlation was observed between chemerin and macrophage inflammatory protein 1-α, which is known to be involved in atherogenesis.…”
Section: Dual Action Of Chemerinsupporting
confidence: 88%
“…[13][14][15] In line with others, we found high chemerin levels to correlate with T2DM and low high-density lipoprotein. 13,14 Furthermore, a positive correlation was observed between chemerin and macrophage inflammatory protein 1-α, which is known to be involved in atherogenesis. 15 Although chemerin is less studied than other adipokines in atherosclerosis, a positive and independent association was noted between chemerin and coronary artery disease.…”
Section: Dual Action Of Chemerinsupporting
confidence: 88%
“…Li et al conducted a meta analysis involving various researchers linking chemerin with metabolic syndrome, obesity and diabetes mellitus and they concluded that chemerin in obesity/metabolic syndrome may be positively correlated with insulin resistance. Chemerin was found to play a role in pathophysiology of obesity and metabolic syndrome [17].…”
Section: Clinical Corrrelation Of Chemerin and Obesity And Diabates Mmentioning
confidence: 99%
“…Further studies have implicated chemerin in exercabating glucose intolerance which later gives rise to diabetes mellitus by enhancing insulin resistance [11]. It was also found that reduction in insulin levels were associated with increasing chemerin levels [17]. Again, Li et al suggested chemerin enhanced an imbalance in lipid metabolism, insulin resistance and altered metabolism of glucose [17].…”
Section: Possible Pathophysiologymentioning
confidence: 99%
See 1 more Smart Citation